One‐Dimensional Photonic Crystal for Surface Mode Polarization Control. Issue 21 (19th August 2022) - Mogni, Erika; Pellegrini, Giovanni; Gil‐Rostra, Jorge; Yubero, Francisco; Simone, Giuseppina; Fossati, Stefan; Dostálek, Jakub; Martínez Vázquez, Rebeca; Osellame, Roberto; Celebrano, Michele; Finazzi, Marco; Biagioni, Paolo
Abstract: Bloch surface waves sustained by truncated 1D photonic crystals (1DPCs) are well known tools for surface‐enhanced spectroscopy. They provide strongly confined fields with uniform distribution over a large surface area, a characteristic exploited in standard refractometric sensing. However, their application to polarization‐sensitive investigations is not straightforward because the transverse electric (TE) and magnetic (TM) surface modes possess distinct dispersion relations, therefore their relative phase is not conserved along propagation and the polarization state of any wave obtained by combining these modes is ill‐defined. In this work, a novel design of a 1DPC is realized in which the TE and TM modes exhibit the same phase velocity over a broadband spectral range and thus their dispersion relations overlap. The capability to simultaneously excite TE and TM modes with a well‐defined phase relation allows the generation of surface waves with a controlled polarization state. This paves the way to polarization‐resolved surface‐enhanced analysis, including, for example, linear and circular dichroism spectroscopy of grafted molecular layers at the photonic crystal surface. Abstract : The experimental demonstration of a modified 1D photonic crystal platform is reported that allows for the matching over a broad spectral range of the dispersion relations of transverse‐electric and transverse‐magnetic Bloch surface wave modes. This result paves the road toward polarization control in evanescent surface waves and their use in polarization‐resolved surface‐enhanced spectroscopy.